The effects of combining erbium, chromium: Yttrium-scandium-gallium-garnet laser irradiation with fluoride application in controlling the progression of enamel erosion - Ahoud AlShamrani; Alhanouf AlHabdan; Malak AlDaweesh; Rahaf bin Hamdan; Randa AlRajhi (Saudi Dental Journal)
Objective: Increasing enamel resistance to acid may be useful for preventing cavitation and could reduce changes in the enamel’s microhardness. Topical fluoride application and laser irradiation promote acid resistance of dental substrates. The aim of the study was to assess the efficacy of erbium, chromium: yttrium-scandium-gallium-garnet laser irradiation in combination with fluoride application to control enamel erosion. Design: Sixty human premolar specimens were prepared (N = 60) and were randomly assigned to 5 groups, twelve specimens in each group (n = 12/group) according to surface treatment. The groups were as follows: group 1 (C): control with no treatment; group 2 (F): application of 1.23% acidulated phosphate fluoride gel alone; group 3 (L): laser irradiation alone; group 4 (F+L): acidulated phosphate fluoride gel followed by laser irradiation; group 5 (L+F): laser irradiation followed by acidulated phosphate fluoride gel. All the specimens were eroded 10 min in citric acid. Baseline measurements were performed using a Vickers microhardness tester before surface treatment. Subsequently, all specimens were subjected to a 60 min erosion-remineralization cycle for five days followed by measurements of the final surface microhardness. Statistical comparisons were performed by a one-way analysis of variance and Tukey’s post hoc analysis. Results: The control, laser, and fluoride + laser groups showed a statistically significant decrease in microhardness values between baseline and post-erosion measurements (P < 0.05), indicating that these treatments could not prevent erosion progression. However, the fluoride and laser + fluoride groups showed a significant increase in microhardness values compared to baseline. Conclusions: Our results suggest that compared to that of the control group, acidulated phosphate fluoride application as well as laser irradiation prior to fluoride application increased enamel surface microhardness and prevented the progression of enamel erosion.